2022
DOI: 10.2186/jpr.jpr_d_21_00045
|View full text |Cite
|
Sign up to set email alerts
|

Novel flapless esthetic procedure for the elimination of extended gingival metal tattoos adjacent to prosthetic teeth: Er:YAG laser micro-keyhole surgery

Abstract: Purpose: This article describes a novel, minimally invasive procedure called Er:YAG laser micro-keyhole surgery (EL-MIKS) that removes metal or amalgam tattoos in the gingiva adjacent to prosthetic teeth without gingival deformity and recession. We aimed to evaluate the clinical efficacy of EL-MIKS for removing metal tattoos and present its long-term treatment outcomes. Methods: The EL-MIKS procedure consists of several steps that are all performed under a microscope. First, a micro-keyhole (1-2 mm diameter) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Because of the antioxidant properties of EMD, as mentioned above [ 56 ], EMD may also have potential benefits for periodontal tissue regeneration therapy in periodontal patients with type 2 DM. Mizutani et al reported that minimally invasive surgery combined with EMD resulted in significant clinical attachment gain and bone filling at comparable levels in the type 2 DM and non-DM groups [ 87 ]. Although various factors may have contributed to these results, the anti-inflammatory and antioxidant effects of EMD may have influenced the periodontal tissues of DM patients, which may be associated with delayed healing after surgery.…”
Section: Clinical Studymentioning
confidence: 99%
“…Because of the antioxidant properties of EMD, as mentioned above [ 56 ], EMD may also have potential benefits for periodontal tissue regeneration therapy in periodontal patients with type 2 DM. Mizutani et al reported that minimally invasive surgery combined with EMD resulted in significant clinical attachment gain and bone filling at comparable levels in the type 2 DM and non-DM groups [ 87 ]. Although various factors may have contributed to these results, the anti-inflammatory and antioxidant effects of EMD may have influenced the periodontal tissues of DM patients, which may be associated with delayed healing after surgery.…”
Section: Clinical Studymentioning
confidence: 99%
“…It is well known that 2.7-3 µm lasers located at the strong absorption peak of water and the atmospheric transparency window in the range of some special wavelengths have potential applications in laser surgery, remote sensing, gas monitoring, detection, spectroscopy measurement, and material processing, etc. [1][2][3] Moreover, they can also be used as pump sources to obtain longer wavelength mid-infrared lasers, such as Fe 2+ -and Dy 3+ -doped lasers and optical parameter oscillator (OPO) lasers. [4][5][6][7] Especially for Q-switched lasers with pulse durations of ns level, which possess much advantages in the field of laser surgery and OPO due to their narrow pulse widths and high peak power.…”
Section: Introductionmentioning
confidence: 99%